Ketertarikan Mahasiswa Patani Melanjutkan Studi Pendidikan Islam di Indonesia - Sehat Sultoni Dalimunthe (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2021)
This research is motivated by curiosity about why Patani people choose to study in Indonesia, while Malaysia is a neighboring country of Patani which is geographically relatively close and also classified as advanced education. The object of research is the past and continues until now, so this study uses the total history method. To get research data, it is mostly used with the documentation method. The documentation method is complemented by the interview method. For Patani students and alumni who can still be found, the data collection techniques used are interviews and observations and are equipped with documentation methods. The results of the study show that the History of Islamic Studies of Patani students in Indonesia from 1963-2019 can be divided into three. First, in 1963-1991, where they studied only on the island of Java and were limited to the cities of Jakarta, Bandung, and Yogyakarta. Second, in 1992-2013, they expanded the study area to Medan and Banda Aceh. Third, in 2014-2019, they studied spread throughout Indonesia. In the first stage, it can be said that they chose the place to study because of the quality factor. In the second stage due to geographical proximity. While the third is because of the available scholarships.